2020
DOI: 10.1155/2020/6666403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dapagliflozin on Glycemic Variability in Patients with Type 2 Diabetes under Insulin Glargine Combined with Other Oral Hypoglycemic Drugs

Abstract: Aim. To evaluate the effect of an inhibitor of sodium-glucose cotransporter 2 (SGLT-2 inhibitor, dapagliflozin) on glycemic variability in type 2 diabetes mellitus (T2D) under insulin glargine combined with oral hypoglycemic drugs, using a continuous glucose monitoring system (CGMS). Methods. This prospective, self-controlled, single-center clinical trial recruited 36 patients with T2D under combined insulin glargine and oral hypoglycemic drugs. General clinical data were collected. Fasting blood glucose (FBG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Furthermore, although multivariate regression analysis was used in all of the included studies, we could not exclude the possibility that there may be residual factors confounding the association, such as the potential influences of different antidiabetic medications and glycemic control strategies. A recent study showed that dapagliflozin (one of the sodium-glucose cotransporter-2 inhibitors) may ameliorate glycemic variability in patients with type 2 diabetes [41], while dapagliflozin has also been shown to benefit cardiac function [42]. Since poor cardiac function has been recognized as an independent risk factor of poor in-hospital outcome of patients after cardiac surgery [43], use of antidiabetic such as dapagliflozin may therefore confound the relationship between acute GV and in-hospital outcome of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although multivariate regression analysis was used in all of the included studies, we could not exclude the possibility that there may be residual factors confounding the association, such as the potential influences of different antidiabetic medications and glycemic control strategies. A recent study showed that dapagliflozin (one of the sodium-glucose cotransporter-2 inhibitors) may ameliorate glycemic variability in patients with type 2 diabetes [41], while dapagliflozin has also been shown to benefit cardiac function [42]. Since poor cardiac function has been recognized as an independent risk factor of poor in-hospital outcome of patients after cardiac surgery [43], use of antidiabetic such as dapagliflozin may therefore confound the relationship between acute GV and in-hospital outcome of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The therapy with SGLT2 inhibitor might be more suitable in type 2 diabetic patients with visceral obesity and poor glycemic control. SGLT2 inhibitor also has a positive influence on glycemic control without the appearance of hypoglycemia [ 42 ]. Our study found that the add-on therapy of both SGLT2 inhibitors and DPP4 inhibitors is associated with a significant beneficial effect (P < 0.001) on FPG, PPBG and HbA1c levels in type 2 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adding dapagliflozin to long-acting insulin and other OHA ameliorated GV in a study including 36 subjects from a Chinese hospital [53]. However, a recently published placebo-controlled, randomized study with 84 Korean patients reported that adding dapagliflozin to basal insulin plus OHA did not show superiority to placebo in terms of GV [54].…”
Section: Glucose Variability Depending On Medicationmentioning
confidence: 98%
“…As for SGLT2 inhibitors, despite limited evidence of the superiority of GV to other OHA, Nomoto et al [ 52 ] showed similar GV between dapagliflozin plus glargine and DPP4 inhibitor plus glargine. In addition, adding dapagliflozin to long-acting insulin and other OHA ameliorated GV in a study including 36 subjects from a Chinese hospital [ 53 ]. However, a recently published placebo-controlled, randomized study with 84 Korean patients reported that adding dapagliflozin to basal insulin plus OHA did not show superiority to placebo in terms of GV [ 54 ].…”
Section: Glucose Variabilitymentioning
confidence: 99%